(untitled) (CIPEEX, 2025)
This study aimed to translate and cross-culturally adapt the Physical Function in Critical Care (PaciFIC) scale, explanatory manual, and demonstration video into Brazilian Portuguese, providing an appropriate functional assessment tool for critically ill patients during their hospital stay in Brazil. The study consisted of the following steps: translation (T1 and T2), synthesis of the initial translation (T1-2), back-translation, and pre-test. The translation was carried out by two bilingual Brazilian translators, followed by an independent back-translation by two native English translators. A committee of three specialists evaluated the versions and created a synthesis in Portuguese. The cultural adaptation involved applying a pre-test with 15 Brazilian physical therapists working in the hospital environment to assess the clarity and equivalence of the translations. The Content Validity Index (CVI) was considered valid if it was above 80%. Of the 29 items evaluated, 18 (62%) achieved valid results according to the CVI. Items that did not reach this coefficient were reviewed and adjusted by the committee to ensure their applicability. The adapted version of the PaciFIC into Portuguese was easy for professionals to understand and can be applied in critical settings.